Health Self-Management Applications in the Work Environment: The Effects on Employee Autonomy - Bonvanie, Anne; Broekhuis, Manda; Janssen, Onne; Maeckelberghe, Els; Wortmann, J. (Hans) C. (Frontiers in Digital Health, 2020)
Organizations increasingly provide Health Self-Management Applications (HSMAs) that provide feedback information to their employees so that they can self-regulate a healthy lifestyle. Building upon Self-Determination Theory, this paper empirically investigates the basic assumption of HSMA use and feedback information, i.e., the provision of perceived autonomy in self-regulating healthy behavior. The two-phase experimental study contained a four-week HSMA intervention with a feedback factor and pretest and posttest measurements of participants’ perceived autonomy. Following the experiment, interviews were conducted with users to gain an in-depth understanding of the findings and in particular the influence of BMI, as a proxy for health condition. Findings reveal that the use of an HSMA does not significantly increase perceived autonomy, and may even reduce it under certain conditions. Providing additional developmental feedback generated more positive results than performance feedback alone. Employees with high BMI sensed a greater loss of autonomy than employees with lower BMI, which is explained by them assigning greater value to general norms, negative emotions when those norms are not met, and increased awareness of their limitations in the environment that hinder their pursuit of health-related behavioral goals.